Enhancements of the dynamic TXOP limit in EDCA through a high-speed wireless campus network - Alam, Mohammed Khorshed; Abdul Latif, Suhaimi; Akter, Mahmuda; Anwar, Farhat; Hasan, Mohammad Kamrul (Springer New York LLC, 2016)
IEEE802.11e is a concrete challenge to providing quality of service (QoS) aimed at interactive multimedia (IMM) applications due to the resource allocation parameter for heterogeneous traffic flows. This parameter is fixed for different specific IMM traffic flows in the IEEE802.11e standard. However, due to the variation in traffic load on wireless campus networks (WCNs), the fixed allocation of the channel resource parameter is not sufficient to guarantee QoS for IMM traffic flows. Thus, many researchers have investigated dynamic regulation of this resource allocation parameter to ensure QoS. However, there are still some unresolved problems with this parameter. This paper introduces an enhanced EDCA resource allocation parameter named dynamic transmission opportunity (TXOP) limit that regulates according to the variation in traffic load over WCN. This work also employs a mathematical modelling approach for the proposed parameter and numerical analysis of the existing and proposed parameters. The evaluation of the proposed model is simulated using Qualnet 5.1. The simulation results show that the proposed scheme allows improving the QoS performance of IMM traffic by reducing endto- end delay. Additionally, the results show that the proposed scheme significantly improves global throughput.